Pengaruh Good Corporate Governance (GCG), Kebijakan Dividen, Dan Struktur Modal Terhadap Nilai Perusahaan - Aris Susetyo; Cahyani Werdaningtyas (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2019)
Firm value has role an important role to the firm. The firm value of going public companies can be showed by stock price. This study aimed to determine the effect of good corporate governance (GCG), dividend policy and capital structure to firm value. In this research good corporate governance (GCG) is proxy by independent composition board of commissioners and amount of members of audit committee, dividend policy is proxy by dividend payout ratio (DPR), capital structure is proxy by debt to equity ratio (DER) and firm value is proxy by Tobins’Q. The population used are LQ 45 Index companies listed in Indonesia Stock Exchange 2011-2016 period which amount 21 companies. Sampling technique used is purposive sampling and obtained by amount as much 11 companies. Analysis technique used is multiple linear regression analysis with SPSS version 22. Hypothesis test use t-statistic to test coefficient of regression partial and also F-statistic to test the truth of collectively influence in level of significance 5%. This research also done a classic assumption test covering normality test, multicolinierity test, autocorrelation test and heteroscedastisity test. The result of study shown that: (1) Good Corporate Governance (GCG) hasn’t effect on firm value, (2) dividend policy has negative and significant effect on firm value, (3) capital structure hasn’t effect on firm value, (4) Good Corporate Governance (GCG), dividend policy and capital structure simultaneously have a positive and significant impact on firm value. Based on the value of adjusted R2, it show that the contribution of variable Good Corporate Governance (GCG), dividend policy and capital structure can be explain by firm value is 26,9%.